2013
DOI: 10.12652/ksce.2013.33.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Properties of Fly ash Concrete Containing Lightly Burnt MgO Powder

Abstract: Although the lightly burnt MgO at 850~1000℃ has expansibility, it does not lead to unsound concrete. The expansion of MgO could compensate for shrinkage of concrete for a long-term, because the hydration of MgO occurs at a slow pace. Recently, the study and application of mineral admixture such as fly ash and blast furnace slag have increased for the hydration heat reduction, durability improvement, and reducing CO2 emission in the construction industry. Thus, it is necessary to research on the concrete that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Therefore, for validation of this concept, it was expected that more hydration products of MgO to be found within the crack walls of proposed self-healing ECC-MgO system. (Choi et al, 2013). Although the TGA/DSC analysis was conducted on ECC-MgO samples at later age (450 days), the degradation peaks of Mg(OH)2 shown in Figure 7-15 (C and D) were relatively small either in sample located in crack walls or within MgO cement paste and thereby these peaks might not be considered (marked by red stars in Figure 7-15).…”
Section: Tga/dsc and Sem Analysis Of Ecc-mgo Self-healing Systemmentioning
confidence: 99%
“…Therefore, for validation of this concept, it was expected that more hydration products of MgO to be found within the crack walls of proposed self-healing ECC-MgO system. (Choi et al, 2013). Although the TGA/DSC analysis was conducted on ECC-MgO samples at later age (450 days), the degradation peaks of Mg(OH)2 shown in Figure 7-15 (C and D) were relatively small either in sample located in crack walls or within MgO cement paste and thereby these peaks might not be considered (marked by red stars in Figure 7-15).…”
Section: Tga/dsc and Sem Analysis Of Ecc-mgo Self-healing Systemmentioning
confidence: 99%
“…It can make concrete produce specific precompression stress characteristics during hardening, reduce volume shrinkage and improve crack resistance. At the same time, it can replace part of the cement and, more importantly, less water is consumed in the hydration reaction (Choi et al, 2013;Choi et al, 2014;Yang et al, 2021). Recently, researchers have found that MEA can compensate for the early shrinkage of UHPC (Li, 2012;Wang et al, 2022), and it has been applied in practical engineering (Li S. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, magnesia-based expansion agents have been used in water conservancy projects, showing good anticracking performance [15,16]. Compared with the expansion agents of calcium oxide and ettringite, the expansion agent of lightly burned magnesium oxide (LBMO) has the advantages of less water demand for hydration, a moderate expansion rate, a long expansion period, delayed microexpansion and a stable hydration product, which makes it more applicable for modern concrete [17][18][19].…”
Section: Introductionmentioning
confidence: 99%